2017
DOI: 10.1177/0954407017713080
|View full text |Cite
|
Sign up to set email alerts
|

Simplified three-dimensional finite element hot-spotting modelling of a pin-mounted vented brake disc: an investigation of hot-spotting determinants

Abstract: Simplified three-dimensional finite element hotspotting modelling of a pin-mounted vented brake disc: an investigation of hot-spotting determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…NAMHS findings seem to be consistent with other research which found 50°C temperature difference at rubbing zones [7]. In contrast, another result reported 5% error between axisymmetric and non-axisymmetric thermal analysis [6]. This might appear due to higher initial velocity used (twice compared to this study).…”
Section: Circumferential Surface Temperature Variationssupporting
confidence: 92%
See 2 more Smart Citations
“…NAMHS findings seem to be consistent with other research which found 50°C temperature difference at rubbing zones [7]. In contrast, another result reported 5% error between axisymmetric and non-axisymmetric thermal analysis [6]. This might appear due to higher initial velocity used (twice compared to this study).…”
Section: Circumferential Surface Temperature Variationssupporting
confidence: 92%
“…Furthermore, spatial surface temperature presented here (Fig. 9) is not observed similar with hot spots and hot bands in other studies [6], which might be due to negligence of thermoelastic contact wear between pad-disc interface, and variation in input parameters. But, compared to traditionally known models, it is believed that the NAMHS had successfully uncovered surface temperature spatial variations at any braking time.…”
Section: Circumferential Surface Temperature Variationssupporting
confidence: 49%
See 1 more Smart Citation
“…[2,25,26]. This case of damage is very often described for brake discs [19,25,27,28]. The consequences of hot spots are judder [16,[29][30][31][32] and the failure of the brake or clutch system [2,33].…”
Section: Introductionmentioning
confidence: 99%
“…Durch Martensitbildung kommt es zu einer Volumenzunahme und zur lokalen Verdickung der Stahllamellen [1,16,17]. Bei Hot Spots an Bremsscheiben werden des Öfteren hohe Spannungen und Risse beschrieben, welche aufgrund hoher thermischer Gradienten entstehen [12,[18][19][20][21].…”
Section: Introductionunclassified